Pengaruh Manajemen Perpajakan, Aset Pajak Tangguhan dan Free Cash Flow Terhadap Manajemen Laba - Kartika, Dwi; Rely, Gilbert; Prayogo, Bambang; Mulyadi; Hasioan Sianipar, Panata Bangar (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2024)
The research aims to examine the effect of Tax Management, Deferred Tax Assets and Free Cash Flow on Profit Management, the population of issuers in the Food & Beverage sub-sector on the Indonesian Stock Exchange for the 2020-2022 period. The research used quantitative data, multiple linear regression, purposive sampling method, obtained from 30 issuers for 3 years, sample 90 data and hypothesis testing using Eviews version 12, the results conclude that (1) Tax Management has no significant effect on Profit Management, (2) Deferred Tax Assets has a negative and significant effect on Profit Management and (3) Free Cash Flow has a negative and significant effect on Profit Management, (4) Tax Management, Deferred Tax Assets and Free Cash Flow simultaneously have a significant effect on Profit Management.